A Cascade Battery: Coupling Two Sequential Electrochemical Reactions in a Single Battery. Issue 44 (17th September 2021) - Dai, Chunlong; Hu, Linyu; Jin, Xuting; Chen, Hao; Zhang, Xinqun; Zhang, Shaohua; Song, Li; Ma, Hongyun; Xu, Maowen; Zhao, Yang; Zhang, Zhipan; Cheng, Huhu; et al.
Abstract: Currently, rechargeable electrochemical batteries generally operate on one reversible electrochemical reaction during discharging and charging cycles. Here, a cascade battery that couples two sequential electrochemical reactions in a single battery is proposed. Such a concept is demonstrated in an aqueous Zn–S hybrid battery, where solid sulfur serves as the cathode in the first discharge step and the generated Cu2 S catalyzes Cu 2+ reduce to Cu/Cu2 O to provide the second discharge step. The cascade battery shows many merits compared to traditional batteries. First, it integrates two batteries internally, eliminating the use of additional inactive connecting materials required for external integration. Second, it can more fully utilize the inactive reaction chamber of the battery than traditional batteries. Third, cascade battery can bypass the challenges of thick solid electrode to access high areal capacity. An ultrahigh areal capacity of 48 mAh cm −2 is achieved even at a low solid cathode loading (9.6 mg cm −2 ). The cascade battery design breaks the stereotype of conventional battery configuration, providing a paradigm for constructing two‐in‐one batteries. Abstract : A cascade battery that couples two sequential electrochemical reactions in a single battery is proposed. It can more fully utilize the inactive reaction chamber than traditional batteries and bypass the challenges of thick solid electrode to access high areal capacity. The cascade battery design breaks the stereotype of conventional battery configuration, paving a way for constructing two‐in‐one batteries.